Attitudes of nurses towards family involvement in the care for patients with cardiovascular diseases. (1st April 2017) - Luttik, M L A; Goossens, E; Ågren, S; Jaarsma, T; Mårtensson, J; Thompson, D R; Moons, P; Strömberg, A; ,
Abstract: Introduction: There is increasing evidence supporting the relationship between family support and patient outcomes. Therefore, involving families in the care of cardiovascular patients is expected to be beneficial for patients. The quality of the encounter with families highly depends on the attitudes of nurses towards the importance of families in patient care. Aim: The aim of this study was to describe the attitudes of nurses towards family involvement in patient care and to investigate the individual contributions of demographic, professional and regional background characteristics. Method: A survey was distributed among cardiovascular nurses attending an international conference in Norway and a national conference in Belgium. Nurses were asked to complete a questionnaire, including the Families' Importance in Nursing Care – Nurses' Attitudes scale. The study population consisted of respondents from Belgium ( n  = 348) and from Scandinavian countries (Norway, Sweden and Denmark; n  = 77). Results: In general, nurses viewed the family as important in care. However, attitudes towards actively inviting families to take part in patient care were less positive. Higher educational level and a main practice role in research, education or management were significantly associated with more positive attitudes. Furthermore, the attitudes of respondents living in Scandinavia were more positive as compared to the attitudes of respondents living in Belgium. Conclusion: Education on the importance of families and active family involvement in patient care seems to be necessary in basic, undergraduate education, but also in clinical practice. More research is necessary in order to explore the cultural and regional differences in the attitudes of nurses towards the involvement of families in patient care.